Quantitative analysis on the wear of monolithic zirconia crowns on antagonist teeth - Zhenyu Tang; Xinyi Zhao; Hui Wang (BMC, 2021)
Abstract Background The present study aimed to quantitate the wear of the highly transparent Yttria-stabilized tetragonal zirconia polycrystals (Y-TZP) ceramic monolithic zirconia crown on the enamel in vivo and discuss the prone position of the wear and the underlying mechanism. Methods A total of 43 patients with 43 posterior teeth were selected for full zirconia crown restoration and examined immediately, at 6 months, and at 1 year after restoration. During the follow-up visit, the fine impression of the patients' monolithic zirconia crowns, the antagonist teeth, the corresponding contralateral natural teeth, the super plaster cast, and epoxy resin model was ontained. The model of epoxy resin was observed under a stereo microscope, and the microstructure parts were observed under a scanning electron microscope. Results After 1 year, the mean depth and volume of wearing of the monolithic zirconia crown were the smallest (all P < 0.01), while those of the antagonist teeth were significantly larger than those of the natural teeth (P < 0.0001), and no significant difference was found among the natural teeth (P = 0.3473, P = 0.6996). The amount of wear after one year was remarkably higher than that at 6 months (P < 0.0001). The microscopic observation revealed the tendency of wearing of the monolithic zirconia crown on the antagonist teeth at the protruding early contact points. Electron micrographs of tooth scars showed that the wearing mechanism of the monolithic zirconia crown on natural teeth was mainly abrasive and fatigue wear. Conclusions Although the self-wearing is insignificant, the monolithic zirconia crown can cause wear of the antagonist teeth via occlusal or early contact significantly; the amount of wearing is higher than that of natural teeth and increases over time. The wearing mechanism is mainly abrasive and fatigue wear.